Wartości moralne w publicystyce Teresy Torańskiej na łamach paryskiej "Kultury" = Moral values in the journalism of Teresa Torańska in the Parisian "Kultura" - Górka, Ewelina (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The article aims to analyse the moral values in the journalism by Teresa Torańska in the Parisian "Kultura", a monthly journal published by Editor Jerzy Giedroyc at the Literary Institute in Paris. Moral values identified with such concepts as the good and freedom have been analysed.
Keywords: wartości moralne; Torańska, Teresa (1944-2013); "Kultura" paryska; moral values; Parisian "Kultura"